‘...and No Loose People to Trouble the Hall’: Oligarchy and the Division of Space in the English Civic Hall to 1640 - Tittler, Robert (History compass, 2012)
Michael McKeon’s chapter on the subdivision of interior, residential spaces shows how concerns for privacy in domestic life played themselves out in the functional division of interior space amongst all ranks of people. This essay suggests that much of the same process might be observed in the civic realm as well as the domestic, and in civic as well as residential spaces. At least to c. 1640, the spatial division and functional specificity of English town halls reflected the requirements of the ruling oligarchies which had come to govern many such communities. Privacy, secrecy, and the emphasis on civic obedience became prime considerations in the design and utilization of such spaces.